In utero delivery of mRNA to the heart, diaphragm and muscle with lipid nanoparticles - Kewa Gao; Jie Li; Hengyue Song; Hesong Han; Yongheng Wang; Boyan Yin; Diana L. Farmer; Niren Murthy; Aijun Wang (Bioactive Materials, 2023)
Nanoparticle-based drug delivery systems have the potential to revolutionize medicine, but their low vascular permeability and rapid clearance by phagocytic cells have limited their medical impact. Nanoparticles delivered at the in utero stage can overcome these key limitations due to the high rate of angiogenesis and cell division in fetal tissue and the under-developed immune system. However, very little is known about nanoparticle drug delivery at the fetal stage of development. In this report, using Ai9 CRE reporter mice, we demonstrate that lipid nanoparticle (LNP) mRNA complexes can deliver mRNA in utero, and can access and transfect major organs, such as the heart, the liver, kidneys, lungs and the gastrointestinal tract with remarkable efficiency and low toxicity. In addition, at 4 weeks after birth, we demonstrate that 50.99 ± 5.05%, 36.62 ± 3.42% and 23.7 ± 3.21% of myofiber in the diaphragm, heart and skeletal muscle, respectively, were transfected. Finally, we show here that Cas9 mRNA and sgRNA complexed to LNPs were able to edit the fetal organs in utero. These experiments demonstrate the possibility of non-viral delivery of mRNA to organs outside of the liver in utero, which provides a promising strategy for treating a wide variety of devastating diseases before birth.